Pengaruh Sistem Reward dan Punishment dalam Meningkatkan Kinerja Pegawai pada Dinas Pemuda dan Olahraga Provinsi Jambi - Bella Ritauli Silalahi; Hendriyaldi Hendriyaldi; Ovie Yanti (Politeknik Kampar, 2025)
This study aims to analyze the influence of the reward and punishment system on the performance of employees at the Jambi Provincial Youth and Sports Office. The study uses a quantitative approach with a survey method of 85 State Civil Apparatus (ASN) employees through census techniques, so that the entire population is used as research respondents. Data was collected using a Likert scale-based questionnaire that has gone through validity and reliability tests to ensure the accuracy of the instrument. The data obtained were then analyzed using multiple linear regression to determine the influence of each variable partially or simultaneously. The results of the study show that rewards and punishments have a positive and significant effect on employee performance, both partially and simultaneously. These two variables contributed 48.6% to employee performance, while the other 51.4% were influenced by other factors outside the research model. These findings affirm the importance of implementing a fair, transparent, and consistent reward and sanction system as an effort to improve work motivation and employee performance in a sustainable manner. In addition, the practical implications of this study show that agency leaders need to design reward and punishment policies that are performance-based and in line with personnel regulations. The implementation of the system is expected to be able to create a competitive work climate, improve discipline, and encourage employees to achieve organizational targets more optimally and professionally.